M & As in the airline industry: emotions flying high. Issue 8 (13th July 2015) - Thomas, Mark; Kummer, Christopher Benjamin
Abstract : Purpose: – Mergers and acquisitions (M & As) are sensitive issues in most industries, but it would seem even more so in airlines. The list of failures or destroyed value in the sector is long. This article outlines three of the main reason why M & As can be a challenge in this industry. Design/methodology/approach: – The article looks at M & As in the airline industry through a key stakeholder and brand identification perspective. It also considers the reaction of airline personnel to merger and analysis the cause of their behaviour. Findings: – Senior management often fails to understand that there is a big difference between negotiating and closing a merger and afterwards making it a success. While they often feel rather exhausted after the long process of discussions, due diligence and many legal aspects including regulatory hurdles – after the announcement the true work starts!